2008
DOI: 10.1097/tp.0b013e31818bc024
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photopheresis After Lung Transplantation: A 10-Year Single-Center Experience

Abstract: We report the largest single-center experience with extracorporeal photopheresis (ECP) for bronchiolitis obliterans syndrome (BOS) and recurrent acute rejection (AR) after lung transplantation. Lung transplant recipients undergoing ECP for BOS and recurrent AR were included (1997-2007). The rate of forced expiratory volume in 1 second (FEV1) decline was used as the primary measure and graft survival post-ECP as the secondary measure of efficacy. Twenty-four transplant recipients were included (BOS, n=12; recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
117
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 15 publications
3
117
1
4
Order By: Relevance
“…86 Though several studies have been performed in patients with BO after HSCT [61][62][63][64][65][87][88][89][90][91] and lung transplantation, [92][93][94] the studies are difficult to interpret because of the heterogeneity in the treatment schedules, diagnostic criteria and response assessment criteria (Table 1). A prospective randomised study of extracorporeal photopheresis treatment performed by Flowers et al 61 revealed a significant improvement of cGVHD in the skin, and indicated a steroid sparing effect on cGvHD in general.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%
“…86 Though several studies have been performed in patients with BO after HSCT [61][62][63][64][65][87][88][89][90][91] and lung transplantation, [92][93][94] the studies are difficult to interpret because of the heterogeneity in the treatment schedules, diagnostic criteria and response assessment criteria (Table 1). A prospective randomised study of extracorporeal photopheresis treatment performed by Flowers et al 61 revealed a significant improvement of cGVHD in the skin, and indicated a steroid sparing effect on cGvHD in general.…”
Section: Extracorporeal Photopheresismentioning
confidence: 99%
“…Усиленная иммуносупрессия с тотальным облучени ем лимфоцитов [173,174] [175,176] могут оказать положительное влияние на снижение легочной функции, обуслов ленное СОБ, но у данных методов, помимо высокой стоимости, имеются значительные побочные эф фекты, поэтому нужны дополнительные клиничес кие исследования для уточнения их эффективности при СОБ. В одноцентровых исследованиях показа но, что в профилактике и лечении СОБ также могут играть роль другие иммуносупрессивные препараты, такие как сиролимус [177], алемтузумаб [178,179] или антитимоцитарный глобулин [180], но для уточ нения места этих препаратов и альтернативных методов долговременной поддерживающей имму носупрессии (например, ингибитора рецепторов mTOR эверолимуса) в профилактике и лечении СОБ нужны дополнительные исследования.…”
Section: ключевые нерешенные вопросы и направления дальнейших исследоunclassified
“…Поляризация Т-клеточно-го ответа в сторону Tх 1 или Tх 2 зависит от типа антиген презентирующей клетки. Дендритные клет-ки (ДК) 1-го типа («моноцитоидные») инициируют Tх 1 -ответ, в то время как ДК 2-го типа («плазмоци- [14] 1997-2007 24 легкое Jaksch P. et al, 2012 [3] 1989-2010 51 легкое Morrell M.R. et al, 2011 [15] 2000-2007 60 легкое Salerno C.T.…”
Section: механизм действия фотофорезаunclassified